O impacto da pandemia da COVID-19 na atenção odontológica do sistema único de saúde em município do Paraná - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
Introduction: From December 2019 onwards, the world was hit by the COVID-19 pandemic, which caused serious impacts, mainly in the health sector. With the aim of reducing the spread of the virus, several measures were adopted, including the suspension of elective Primary Care services, which led to the holding back of services considered non-emergency. Objectives: This study aimed to analyze the impact of the COVID-19 pandemic on dental care provided by the Unified Health System in a municipality in the interior of Paraná. Objectives: This study aimed to analyze the impact of the COVID-19 pandemic on dental care provided by the Unified Health System in a municipality in the interior of Paraná. Materials and method: This is an ecological type study. Information regarding COVID-19 in the researched municipality was obtained from the Coronavirus Bulletins (COVID-19) from the Paraná Department of Health. The municipality's data regarding dental treatments (elective and urgent) were obtained from the Information Technology Department of the Unified Health System (DATASUS). The period of analysis was 2019 (before the pandemic) and the years 2020 to 2022. For comparison purposes, the same data for the same period were collected for the State of Paraná. The data were analyzed using descriptive statistics and statistical tests were performed to calculate comparisons and correlations Crude and standardized incidence and mortality rates were calculated. These rates were compared to dental procedures. Results: The pandemic experienced in recent years actually affected dental production with a significant drop in both elective and emergency procedures for the municipality of Prudentópolis and the state of Paraná in 2020, 2021 and 2022 compared to 2019. The biggest drops were for restoration of deciduous teeth and long-term dressing in Prudentópolis and supragingival scaling, smoothing and polishing and pulpotomy in Paraná. The correlation was negative between the incidence of COVID-19 and elective and urgent procedures in Paraná in 2021 and 2022 and negative between mortality from COVID- 19 and elective and urgent procedures in Paraná in 2021. Prudentópolis did not show a significant correlation. Conclusion: The results of this study indicate that the COVID- 19 pandemic had a significant impact on the production of dental procedures in Paraná, both at the municipal and state levels in the SUS. Both elective and urgent procedures have decreased as the incidence of COVID-19 has increased, especially in the years 2021 and 2022. These findings highlight the need for appropriate policies and interventions to mitigate the impacts of the pandemic on the provision of dental services and ensure continued and equitable access to oral care.
Keywords: Assistência odontológica; Infecções por Coronavírus; Sistema Único de Saúde; Dental care; Coronavirus infections; Health Unic System; CNPQ::CIENCIAS DA SAUDE